Prevalence of Individuals With Deafblindness and Age-Related Dual-Sensory Loss. (January 2022) - Minhas, Renu; Jaiswal, Atul; Chan, Serena; Trevisan, Jessica; Paramasivam, Abinethaa; Spruyt-Rocks, Roxanna
Introduction: The authors of this paper have compiled a report on the prevalence of deafblindness and dual-sensory loss based on the review of existing estimates. The purpose is to inform readers of the importance of using consistent, well-researched definitions and survey questions in future prevalence studies. Methods: Articles were extracted through ProQuest and EBSCOhost, online library databases of Cambrian College and Laurentian University. Keywords search included "deafblindness, " "dual-sensory impairment, " "dual-sensory loss, " "age-related, " "congenital, " "acquired, " and "prevalence." Additionally, the authors conducted a search with Google for research reports and Google Scholar for other relevant peer-reviewed articles. Results: This review provides a current overview of prevalence estimates of deafblindness and age-related dual-sensory loss around the world, examining 19 articles or reports published over the last 20 years (2000–2020) in 18 countries, including the European Union (consisting of 8 countries). In line with the prevalence estimates by the World Federation for the Deafblind global report 2018, the review indicates an estimated 0.2–2% prevalence of dual-sensory impairment and underscores varying ranges of prevalence among populations, studies or countries, age groups, and types of deafblindness. The review highlights that the prevalence of deafblindness or dual-sensory loss was often not comparable across studies, but it is clear that the prevalence of dual-sensory impairment increases with age. The studies varied in methods (e.g., population surveys, cross-sectional, and longitudinal studies). Implication for Practitioners: The review provides evidence of varying ranges of prevalence rates. Future prevalence studies may benefit from consistent definitions, standard data-collection tools to do better comparisons across countries, and identify factors that predict higher or lower prevalence rates among populations and age groups.